2017
DOI: 10.3892/ol.2017.6686
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the microRNA-mRNA regulatory network in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a common myelogenous malignancy in adults that is often characterized by disease relapse. The pathophysiological mechanism of AML has not yet been elucidated. The present study aimed to identify the crucial microRNAs (miRNAs/miRs) and target genes in AML, and to uncover the potential oncogenic mechanism of AML. miRNA and mRNA expression-profiling microarray datasets were downloaded from the Gene Expression Omnibus database. Differential expression analysis was performed and a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…The KEGG enrichment analysis revealed that DEGs were enriched in pathways of cancer, PI3K-Akt signaling pathway, and transcriptional misregulation in cancer. Consistent with previous studies, the above pathways have been reported that affect the pathogenesis and prognosis of AML [ 30 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…The KEGG enrichment analysis revealed that DEGs were enriched in pathways of cancer, PI3K-Akt signaling pathway, and transcriptional misregulation in cancer. Consistent with previous studies, the above pathways have been reported that affect the pathogenesis and prognosis of AML [ 30 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the KEGG enrichment analysis showed that DEGs were notably abundant in pathways of cancer, ECM-receptor interaction, and cAMP signal. While the cancer pathway was expected and is in line with a previous study [22], it is unclear how the ECM-receptor interaction pathway and the cAMP signaling pathway affect the pathogenesis and prognosis of AML. ECM-receptor interaction pathway enrichment was reported in esophageal squamous cell carcinoma [23].…”
Section: Discussionsupporting
confidence: 69%
“…These are a broad class of regulatory molecules, which comprises both long‐noncoding RNAs (lncRNAs) and small RNAs, like microRNAs (miRNAs). Two recent studies have tried to assess the contributions of these molecules to AML development and found that not only are they altered, but they also have an impact on prognosis 89,90 . Analyzing RNA‐seq public available data for AML, Pan et al.…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%